2019
DOI: 10.5039/agraria.v14i2a5639
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics of Talinum triangulare (Jacq.) Willd leaves and physicochemical assessment of flour

Abstract: Talinum triangulare (Jacq.) Willd (Talinaceae) is a plant cultivated in Africa, Asia, and Latin America for medicinal and food purposes. This study aimed to assess the drying kinetics of T. triangulare leaves under different temperatures and the physicochemical characteristics of flour produced. Leaves were dried to constant weight in an oven at temperatures of 50, 60, 70 and 80 °C. Drying results were adjusted to mathematical models used to represent the drying of agricultural products. After drying, leaves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It can be observed that all models, except Wang and Singh, showed R 2 values higher than 0.970, indicating that they are adequate for predicting the drying kinetics of the material. Martins et al (2015), Alexandre et al (2019) and Santos et al (2020), stated that R 2 > 0.95 indicates a good representation of the results through mathematical models, but evaluating only this parameter does not constitute a good criterion for selecting nonlinear models, hence requiring joint evaluation of other statistical parameters such as MSD and χ 2 .…”
Section: Results and Discu And Discu And Discu And Discussion Ssion S...mentioning
confidence: 99%
“…It can be observed that all models, except Wang and Singh, showed R 2 values higher than 0.970, indicating that they are adequate for predicting the drying kinetics of the material. Martins et al (2015), Alexandre et al (2019) and Santos et al (2020), stated that R 2 > 0.95 indicates a good representation of the results through mathematical models, but evaluating only this parameter does not constitute a good criterion for selecting nonlinear models, hence requiring joint evaluation of other statistical parameters such as MSD and χ 2 .…”
Section: Results and Discu And Discu And Discu And Discussion Ssion S...mentioning
confidence: 99%